Analisis Penerapan Smart City Menggunakan IT Balanced Scorecard - Adhe Ronny Julians; Melkior Nikolar Ngalumsine Sitokdana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Mimika District Population and Civil Registration Office continues to issue new breakthroughs, especially smart city programs, in order to bring services closer to the community more precisely, efficiently, effectively, responsively, and continue to increase innovation and adoption of integrated technologies.. The purpose of this study is to analyze the conditions of smart city implementation that has been running in the research site using 4 perspectives contained in the IT Balanced Scorecard. This study uses a qualitative descriptive approach, supported by observations and interviews to strengthen the research. The results revealed that the perspective of the company's contribution, user orientation, and future orientation is good by providing excellent service comfort and speed, as well as how these services work so as to increase citizens' satisfaction with intelligent system service products. But from an operational refinement perspective, there are problems with internet networks that have not been optimized.